2017
DOI: 10.1017/age.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Policy Changes on Milk and Beverage Consumption of Texas WIC Children

Abstract: Major changes in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) food packages that were implemented in 2009 included reductions in the amount of milk and 100% juices, as well as the removal of whole milk from food packages. In analyzing the effect of these changes on the beverage consumption of Texas WIC children ages two to four, we found a significant decrease in the amount of whole milk consumed, and this decrease was partially offset by the increase in the amount of lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They found that the revision was associated with healthier eating patterns including increased frequencies of fruit, vegetable, whole grain and reduced-/low-fat milk consumption. The authors later conducted a similar analysis for Texas WIC children aged 2 to 4 (Ishdorj and Capps 2017). They found the amount of reduced/low-fat milk increased to partially offset the reduction in whole milk.…”
Section: The Literature On the 2009 Food Package Revisionmentioning
confidence: 97%
“…They found that the revision was associated with healthier eating patterns including increased frequencies of fruit, vegetable, whole grain and reduced-/low-fat milk consumption. The authors later conducted a similar analysis for Texas WIC children aged 2 to 4 (Ishdorj and Capps 2017). They found the amount of reduced/low-fat milk increased to partially offset the reduction in whole milk.…”
Section: The Literature On the 2009 Food Package Revisionmentioning
confidence: 97%